1999
DOI: 10.1111/j.1095-8649.1999.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of agonistic behaviour and vocalization in croaking gouramis

Abstract: The development of agonistic behaviour and vocalization in the croaking gourami Trichopsis vittata was studied from hatching to sexual maturity (4 months of age). Initial interactions started when fry were 11 days old and consisted of approach and flight in a feeding context. More complex threat patterns appeared during dyadic encounters as fish grew older. Lateral display (spreading of median fins in a lateral position) first occurred during the third week, circling shortly afterwards and pectoral fin beating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…In Myripristis , we showed the number of pulses and their amplitudes were lower in the larvae than in the adults. Although the mechanisms are not the same, these results are in concordance with studies involving fishes from other taxa: the croaking gourami T. vittata [ 16 , 39 ] and the gurnard E. gurnardus [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…In Myripristis , we showed the number of pulses and their amplitudes were lower in the larvae than in the adults. Although the mechanisms are not the same, these results are in concordance with studies involving fishes from other taxa: the croaking gourami T. vittata [ 16 , 39 ] and the gurnard E. gurnardus [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…The dominant frequency of sounds is negatively correlated with body size in representatives of all families investigated so far, for example, in pomacentrids - Stegastes partitus , Dascyllus albisella, Amphiprion akallopisos, A. clarkii, A. frenatus , A. ocellaris , [ 23 , 26 , 34 , 35 ], osphronemids - Trichopsis vittata , T. pumila and T. schalleri [ 17 , 21 , 22 ], sciaenids - Cynoscion regalis [ 36 ], triglids - Eutrigla gurnardus [ 25 ], and toadfishes - Halobatrachus didactylus [ 19 ]. Fine et al [ 37 ] found a decrease of center frequency in the ictalurid catfish Ictalurus punctatus .…”
Section: Discussionmentioning
confidence: 99%
“…Some evidences attest that dominant frequency and pulse duration are related to fish size in the A. akallopisos: larger individuals produce lower frequency and longer duration pulses than smaller individuals. In the croaking gourami Trichopsis vittata (Cuvier) for example, sound duration increases during ontogeny whereas dominant frequency decreases (Henglmüller & Ladich, 1999). In the grey gurnard Eutrigla gurnardus (L.), sound production changes from small juveniles to large adults during competitive feeding (Amorim & Hawkins, 2005).…”
mentioning
confidence: 99%